Akirin Is Required for Muscle Function and Acts Through the TGF-β Sma/Mab Signaling Pathway in Caenorhabditis elegans Development. Issue 1 (1st January 2020) - Bowman, Richard; Balukoff, Nathan; Clemons, Amy; Koury, Emily; Ford, Talitha; Baxi, Kunal; Egydio de Carvalho, Carlos; Smolikove, Sarit
Abstract: Akirin, a conserved metazoan protein, functions in muscle development in flies and mice. However, this was only tested in the rodent and fly model systems. Akirin was shown to act with chromatin remodeling complexes in transcription and was established as a downstream target of the NFκB pathway. Here we show a role for Caenorhabditis elegans Akirin/AKIR-1 in the muscle and body length regulation through a different pathway. Akirin localizes to somatic tissues throughout the body of C. elegans, including muscle nuclei. In agreement with its role in other model systems, Akirin loss of function mutants exhibit defects in muscle development in the embryo, as well as defects in movement and maintenance of muscle integrity in the C. elegans adult. We also have determined that Akirin acts downstream of the TGF-β Sma/Mab signaling pathway in controlling body size. Moreover, we found that the loss of Akirin resulted in an increase in autophagy markers, similar to mutants in the TGF-β Sma/Mab signaling pathway. In contrast to what is known in rodent and fly models, C. elegans Akirin does not act with the SWI/SNF chromatin-remodeling complex, and is instead involved with the NuRD chromatin remodeling complex in both movement and regulation of body size. Our studies define a novel developmental role (body size) and a new pathway (TGF-β Sma/Mab) for Akirin function, and confirmed its evolutionarily conserved function in muscle development in a new organism.